The heartbeat library - Imai Messina, Laura (The Overlook Press, 2024)
"On the peaceful Japanese island of Teshima there is a library where the heartbeats of visitors from all around the world are collected. In this small, isolated building, the pulses of people who are still alive or who have already passed away continue to echo. Several miles away, in the ancient city of Kamakura, two lonely souls meet: Shuichi, a forty-year-old illustrator, who returns to his hometown to fix up the house of his recently deceased mother, and eight-year-old Kenta, a child he finds wandering like a shadow around it. Day by day, the trust between Shuichi and Kenta grows, until they discover they share a bond that will tie them together for life. Their journey will lead them to Teshima and to the library of heartbeats..."